Youth Multi-Association Participation and Public Space: Evidence from the Chilean Case - Daniel Carmen (GoAcademica Research & Publishing, 2023)
The objective of the article is to expose a set of reflections and empirical findings related to the phenomenon of youth associative participation and its relationship with the development of greater civility as a condition of democratic strengthening. Within this framework, a series of findings related to the phenomenon of